Severe Hypokalemia in the Intensive Care Unit: Case Series on Potassium Correction Strategies and Clinical Outcomes - Daniswara, Daniswara; Prasamya, Erlangga (Jurnal Anestesi Perioperatif, 2025)
Hypokalemia is one of the electrolyte disorders that often occurs in intensive care units (ICUs), defined as a serum potassium concentration below 3.5 mmol/L. Its severity is classified as mild (3.0–3.4 mmol/L), moderate (2.5–3.0 mmol/L), and severe (<2.5 mmol/L). Hypokalemia occurs when the body loses too much potassium due to several factors such as vomiting, excessive diarrhea, kidney disease, hormonal disorders, or taking diuretic drugs. Symptoms of hypokalemia generally appear when serum potassium is less than 3.0 mmol/L, ranging from mild weakness to life-threatening cardiac arrhythmias. In critically ill patients, untreated severe hypokalemia can lead to cardiac arrhythmias, respiratory arrest, and renal dysfunction, with a higher risk of complications and mortality in patients with hypotension, diabetes, or chronic kidney disease. This case series involved six ICU patients with severe hypokalemia (K⁺ ≤1.8 mmol/L) who underwent rapid potassium correction at a rate of 10–40 mEq/hour adjusted to the patient's clinical severity. In patients with ventricular arrhythmias, initial correction of 2 mEq/minute was followed by 10 mEq over 5–10 minutes. Most patients showed clinical improvement, while worse outcomes were observed in patients with hyperthyroidism and after return of spontaneous circulation (ROSC). This case series highlights the importance of individualized potassium replacement strategies, immediate intervention, and careful monitoring to prevent life-threatening complications and improve outcomes in patients with severe hypokalemia in the ICU.